(untitled) (Palíndromo, 2020)
The present text describes and analyzes the performance “In search of the master’s degree”, 2005 - 2007, series produced between the academy and the street, and how this process was transformed by the author/artist into an autobiographical duracional performance. The act of writing about performance art requires a multidisciplinary approach involving several areas of knowledge on borders of the art and the life, so the use of poetic language and me- talanguage were resources explored throughout the textual composition.